1989
DOI: 10.1021/jf00088a008
|View full text |Cite
|
Sign up to set email alerts
|

Exothermic transitions of glycinin determined by differential scanning calorimetry

Abstract: Thermal properties of soy glycinin were investigated in the presence and absence of the reducing agent 2-mercaptoethanol. An endothermic transition was observed without reducing agent, but an exotherm, followed by a relatively small endotherm, was seen in the presence of 0.05 M 2-mercaptoethanol. The presence of the exotherm was dependent on the glycinin concentration and disappeared a t 6% protein concentration. The peak maximum temperatures of the endotherms in the presence and absence of 2-mercaptoethanol w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…With increasing pH, a significant (P < 0.05) increase in the enthalpy of denaturation was observed. The enthalpies of transitions found in this study are generally in good agreement with those reported in the literature (7-17 J/g for different ionic strengths) (Lakemond, de Jongh, Hessing, Gruppen, & Voragen, 2000b;Koshiyama, 1980Koshiyama, -1981Marshall & Zarins, 1989).…”
Section: Differential Scanning Calorimetry (Dsc)supporting
confidence: 91%
“…With increasing pH, a significant (P < 0.05) increase in the enthalpy of denaturation was observed. The enthalpies of transitions found in this study are generally in good agreement with those reported in the literature (7-17 J/g for different ionic strengths) (Lakemond, de Jongh, Hessing, Gruppen, & Voragen, 2000b;Koshiyama, 1980Koshiyama, -1981Marshall & Zarins, 1989).…”
Section: Differential Scanning Calorimetry (Dsc)supporting
confidence: 91%
“…Unlike CPI10, a great exothermic change of baseline was detected at °C. This exotherm could be associated with an aggregation process of previous denatured proteins (Fitzsimons, Mulvihill & Morris, 2007, Marshall & Zarins, 1989, Lohner & Esser, 1991). The energy of endotherms obtained in CPI12 was considerably lower than in CPI10, 0.7±0.5 J/g (dry basis).…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
“…The most widely used method for this application is DSC. Most studies have focused on systems of starch in excess water (Stevens and Elton, 1971;Slade, 1984;Biliaderis et al, 1986;Yost and Hoseney, 1986;Slade andLevine, 1987, 1991;Marshall and Normand, 1991;Liu and Lelievre, 1991;Huang et al, 1994;Buera et al, 1998); only a few studies have been carried out in starch/water systems with a low MC (Slade, 1984;Slade andLevine, 1987, 1991;Zeleznak and Hoseney, 1987;Liu and Lelievre, 1991;Kalichevsky et al, 1992;Perdon et al, 2000). Slade (1984), Zeleznak and Hoseney (1987), and Slade andLevine (1987, 1991) showed that T g of wheat starch is extremely sensitive to MC.…”
mentioning
confidence: 99%